2007
DOI: 10.1007/s10661-007-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of O3, NO2, SO2, CO and PM10 measured in Belgrade urban area

Abstract: O(3), NO(2), SO(2), CO and PM(10) concentrations, simultaneously determined for the first time in Belgrade urban area in the autumnal period of 2005, are presented. The obtained results display similar behaviour of SO(2), NO(2), CO, PM(10) opposite from that of O(3). The weekend effect was also investigated showing diminution of average daily concentrations of SO(2), NO(2), PM(10) and CO for 72, 40, 37 and 42% respectively, and increase of the average daily concentration of O(3) for 56%. Influence of meteorolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 19 publications
8
29
0
1
Order By: Relevance
“…Periods with higher temperature and lower humidity usually lead to higher levels of O 3 and lowers level of NO 2 in the atmosphere and vice versa. Similar changes in O 3 and NO 2 concentration levels with respect to the climatic variables have already been described in literature (Lieu et al 1987;Chan et al 2001;Martin et al 2009;Ahmad et al 2011 Atkins and Lee (1995), Wahid et al (1995aWahid et al ( , 1995b, Markovic et al (2008), and Shan et al (2009). Similar variations in NO 2 and O 3 concentration with climatic variables were observed in Spain.…”
Section: Resultssupporting
confidence: 86%
“…Periods with higher temperature and lower humidity usually lead to higher levels of O 3 and lowers level of NO 2 in the atmosphere and vice versa. Similar changes in O 3 and NO 2 concentration levels with respect to the climatic variables have already been described in literature (Lieu et al 1987;Chan et al 2001;Martin et al 2009;Ahmad et al 2011 Atkins and Lee (1995), Wahid et al (1995aWahid et al ( , 1995b, Markovic et al (2008), and Shan et al (2009). Similar variations in NO 2 and O 3 concentration with climatic variables were observed in Spain.…”
Section: Resultssupporting
confidence: 86%
“…The correlation coefficient between relative humidity and SO 2 , NO x , and CO was also found to be negative or weak (Table S3). The comparatively similar association between SO 2 , NO x , and CO and meteorological parameters (temperature and relative humidity) was also found at other urban site (Marković et al 2008). Contrarily, O 3 followed a positive linear relationship with temperature, except in post-monsoon season while the strong negative with the relative humidity in all seasons.…”
Section: Resultssupporting
confidence: 78%
“…from July to September the ozone concentration in the atmosphere decreased with increase in rate of rain fall due to dispersion and transportation of pollutants in the atmosphere leads to dilution of pollutants in the atmosphere. Similar relationship of ozone concentration levels with meteorological variables have previously been reported by Atkins and Lee (1995), Wahid et al (1995a, 1995b) Chan, So, and Samad (2001, Ghauri, Lodhi, and Mansha (2007), Markovic et al (2008), Shan et al (2009) and Martin et al (2010). Multiple regression analysis (Table 3) showed that ozone concentration is greatly influenced by the independent climatic variables i.e.…”
Section: Relationship With Meteorological Variablessupporting
confidence: 84%